2017
DOI: 10.4103/jcrt.jcrt_140_17
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment is an effective approach for patients with synchronous multiple primary lung cancers

Abstract: SMPLC could be considered to be a local disease rather than the systemic disease. Surgical treatment is an effective approach for patients with SMPLC. Mutational status of EGFR could be used as a diagnostic criterion, especially in patients with SMPLA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…These were basically consistent with other researches [2][3][4][5][6][7]. The research of Shintani, T. et al [13] found that in SMPLC patients only treated with stereotactic body radiotherapy (SBRT), the 3-year OS rate and DFS rate were 69.1% and 43.2%, far lower than the surgical-based comprehensive treatment.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These were basically consistent with other researches [2][3][4][5][6][7]. The research of Shintani, T. et al [13] found that in SMPLC patients only treated with stereotactic body radiotherapy (SBRT), the 3-year OS rate and DFS rate were 69.1% and 43.2%, far lower than the surgical-based comprehensive treatment.…”
Section: Discussionsupporting
confidence: 88%
“…The research of Shintani, T. et al [13] found that in SMPLC patients only treated with stereotactic body radiotherapy (SBRT), the 3-year OS rate and DFS rate were 69.1% and 43.2%, far lower than the surgical-based comprehensive treatment. Other studies also supported this conclusion [14][15].Comprehensive studies had shown that the prognosis of patients with SMPLC was better than that of patients with lung cancer recurrence or metastasis [2][3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…We observed that the material-suppressed iodine image, as a virtual non-enhanced CT, which has a perfect image match, can reduce the measurement error from the position change of SPNs in different phases. We also found that the area under the curve of the enhancement degree [21,22], iodine concentration and 40 keV and 50 keV monochromatic the arterial phase were similar, which may be due to the linear correlation between CT attenuation value and iodine concentration for both monochromatic and polychromatic images [23]; thus, we did not do a series of parallel tests.…”
Section: Discussionmentioning
confidence: 91%